Pengaruh Employee Engagement dan Kepuasan Kerja terhadap Organizational Citizenship Behavior serta Dampaknya terhadap Kinerja Karyawan pada Akademi Maritim Nusantara Cilacap - Hari Sucahyowati (Lembaga Penelitian dan Pengabdian Masyarakat, Akademi Maritim Nusantara Cilacap, 2023)
The influence of employee engagement and job satisfaction on organizational citizenship behavior and its impact on the performance of employees at the Maritime Academy of Nusantara Cilacap is the subject of this research. Organizational citizenship behavior is used as an intermediate variable in this study. Data collection was carried out by distributing questionnaires on the Likert scale to all employees of the Maritime Academy of Nusantara Cilacap. The data collection method involved 80 lecturers and staff members of the Maritime Academy of Nusantara Cilacap who were surveyed for their opinions through questionnaires. The analysis method used in this research is Partial Least Square (PLS) with SmartPLS version 3.2.9 software. The research results indicate that organizational citizenship behavior is influenced by employee engagement. Furthermore, job satisfaction also has a positive impact on organizational citizenship behavior. Employee engagement also contributes positively to employee performance, as does job satisfaction, which has a positive impact on organizational citizenship behavior and overall performance.